Corporate governance in Malaysia : contemporary issues - Noor Afza Amran, contributor 405019; Basariah Salim, contributor 406260; Zaleha Othman, contributor 551680; Nor Shaipah Abd Wahad, contributor 551681; Hasnah Kamardin, contributor 405166; Rokiah Ishak, contributor 406245 (Petaling Jaya, Selangor : Pearson, 2012)
Includes bibliographical references.